Menjaring Makna Yad dalam Al-Qur’an Perspektif Semantik Toshihiko Izutsu - Najamuddin, M. Hilmi (STAI Darul Kamal NW Kembang Kerang, 2024)
This article discusses the semantic meaning of the word yad in the Qur'an. The author uses a semantic approach, namely an analytical study of the key terms of a language with a view that ultimately arrives at a conceptual understanding or world view. This research uses a qualitative research method with a descriptive analytical discussion method with a type of library research. The word yad in the Qur'an is repeated 113 times, and is found in 103 verses, with various forms, namely mufrad (singular) 16 times, mutsanna (double) 33 times, and plural (compound) 64 times. Based on Toshihiko Izutsu's semantics, the author concludes that the basic meaning of the word yad is the hand, part of the human body, while the relational meaning from the syntagmatic analysis of the word yad is kudrah, strength, in front and gift. Among the paradigmatic relational meanings are Al Kaff and Al Dzira. In the pre-Qur'anic period, the word yad meant hands, part of the human body. In the Qur'anic period, the hand can shift to meanings that have spiritual value (bakhil, benefactor). Meanwhile, in the post-Quranic period, the word yad did not experience a significant change in meaning. From several analyzes that have been carried out above, it can be seen that the waltanschauung or worldview of the word yad, namely the hand, is materially part of the human body and also yad which has a shift in meaning in the spiritual realm such as generosity, piety, grace and strength.